The solvent extraction behaviour of chromium with Bis (2,4,4-trimethylpentyl) phosphinic acid (Cyanex [R] 272) - Lanagan, Matthew D. (Curtin University, 2003)
The bulk of the world's known nickel reserves are contained in laterite ores but sulphidic ores remain the main source of the Western world's nickel production. With the continuing increase in nickel consumption and the depletion of sulphidic ores, the traditional source of nickel, the extraction of nickel from lateritic ores has been the subject of research interest worldwide. Advances in pressure acid leaching (PAL) technology have resulted in significant commercial attempts to extract nickel from these ores. Leaching the ore with sulphuric acid at elevated temperatures and pressures allows almost complete dissolution of the nickel and cobalt, a valuable byproduct of these ores, but yields highly contaminated pregnant leach solutions. Separating and purifying the nickel and cobalt from these solutions remains a hindrance to full commercial production. Several purifying techniques have been commercialised but all suffer from continuing technical problems. Among them, however, the direct solvent extraction (DSX) technique offers several advantages. Direct solvent extraction involves the separation of the nickel and cobalt directly from the partially neutralised pregnant liquor stream (PLS) by solvent extraction with Cyanex(R) 272 as the extractant. However certain contaminants adversely affect the solvent extraction process. Among them is chromium and little is known about the solvent extraction behaviour of this metal. The present work investigated the solvent extraction of chromium with Cyanex(R) 272. It was found that the solvent extraction behaviour of chromium(III) and chromium(VI), both of which could be found in PAL-generated PLS, are distinctly different.For chromium(III), solvent extraction tests showed that (a) it is extracted in the pH range 4-7; (b) the extraction is partly influenced by diffusion; (c) the apparent equilibration time is significantly longer than most transition metals; (d) increases in temperature from 22 to 40 C resulted in increases in the extraction; (e) the pH0.5 increases in the order nitrate < chloride < sulphate in the presence of these anions; (f) the presence of acetate depresses extraction of chromium(III) when the solution is allowed to stand before extraction; (g) in the PLS, chromium(III) precipitated at lower pH than that predicted by the solubility product principle; and (h) the pH0.5 decreases as the Cyanex(R) 272 concentration increases. Chromium(III) is initially extracted by solvation of its inner sphere complex, which then undergoes further reaction in the organic phase leading to the formation of a much more stable species that is difficult to strip. A reaction scheme together with a description of both the initially extracted and resulting stable species is proposed. Extraction of chromium(VI), on the other hand, (a) occurs at pH less than 2 by solvation of chromic acid; (b) is independent of the aqueous phase composition; (c) does not occur in the pH range (3-6) used in the separation of nickel and cobalt. The latter is irrespective of temperature up to 40 C, the use of industrial PLS as the aqueous phase or the presence of an anti-oxidant in the organic phase. The stripping of chromium(III) from a loaded organic phase can be achieved using 1-4 mol L-1 mineral acids provided the stable organic species have not formed making industrial scale stripping of chromium(III) from Cyanex(R) 272 difficult. The exact composition of the aqueous phase during extraction affects the stripping efficiency.